All’s Bad That Ends Bad: There Is a Peak-End Memory Bias in Anxiety - Müller, Ulrich W. D.; Witteman, Cilia L. M.; Spijker, Jan; Alpers, Georg W. (Frontiers in Psychology, 2019)
The peak-end memory bias has been well documented for the retrospective evaluation of pain. It describes that the retrospective evaluation of pain is largely based on the discomfort experienced at the most intense point (peak) and at the end of the episode. This is notable because it means that longer episodes with a better ending can be remembered as less aversive than shorter ones; this is even if the former had the same peak in painfulness and an overall longer duration of pain. Until now, this bias has not been studied in the domain of anxiety despite the high relevance of variable levels of anxiety in the treatment of anxiety disorders. Therefore, we set out to replicate the original studies but with an induction of variable levels of anxiety. Of 64 women, half watched a clip from a horror movie which ended at the most frightening moment. The other half watched an extended version of this clip with a moderately frightening ending. Afterwards, all participants were asked to rate the global anxiety which was elicited by the video. When the film ended at the most frightening moment, participants retrospectively reported more anxiety than participants who watched the extended version. This is the first study to document that the peak-end bias can be found in the domain of anxiety. These findings require replication and extension to a treatment context to evaluate its implications for exposure therapy.